2017
DOI: 10.1016/j.cej.2016.05.127
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Diphenhydramine with different AOPs including photo-Fenton at circumneutral pH

Abstract: h i g h l i g h t s Diphenhydramine degradation by different AOPs is compared. Power and wavelengths of lamps are important in the contaminant degradation. Fenton and photo-Fenton can work at initial circumneutral pH. Black blue lamps gave the best results in diphenhydramine abatement. Acidification of the solution is avoided by the addition of Resorcinol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…8). 32,33 In summary, from the intermediates determined it appears that the oxidation process occurs mainly through the hydroxyl radicals. However, the results from the scavenger experiments indicated that the superoxide anions also play an important role.…”
Section: Identication Of Degradation Products and Pathwaysmentioning
confidence: 95%
See 1 more Smart Citation
“…8). 32,33 In summary, from the intermediates determined it appears that the oxidation process occurs mainly through the hydroxyl radicals. However, the results from the scavenger experiments indicated that the superoxide anions also play an important role.…”
Section: Identication Of Degradation Products and Pathwaysmentioning
confidence: 95%
“…As shown in Table 3, the photocatalytic process leads to the formation of m/z 183, m/z 272, and m/z 167, which were also detected in the previous studies. 15,31,33 Among the observed products, m/z of 272 could be attributed to the hydroxylation of DP (m/z 256) (Fig. 8).…”
Section: Identication Of Degradation Products and Pathwaysmentioning
confidence: 98%
“…Despite these common techniques, research interest also has been devoted towards exploring promising technologies able to destroy the hazardous organic compounds, rather than transferring the pollutants from one phase to another [6]. Such methods are known as advanced oxidation processes (AOPs) that imply the destructive oxidation of organic pollutants [6][7][8]. Hence, AOPs deal with homogenous catalysis and photocatalysis (Fenton, H 2 O 2 /UV, Fenton-like [7,8]), heterogeneous catalysis (CWPO-Catalytic Wet Peroxide Oxidation) [9], heterogeneous photocatalysis (TiO 2 /UV) [6,8] and others (e.g., catalytic ozonation [10]).…”
Section: Introductionmentioning
confidence: 99%
“…Such methods are known as advanced oxidation processes (AOPs) that imply the destructive oxidation of organic pollutants [6][7][8]. Hence, AOPs deal with homogenous catalysis and photocatalysis (Fenton, H 2 O 2 /UV, Fenton-like [7,8]), heterogeneous catalysis (CWPO-Catalytic Wet Peroxide Oxidation) [9], heterogeneous photocatalysis (TiO 2 /UV) [6,8] and others (e.g., catalytic ozonation [10]). According to the AOPs mechanism, the toxic pollutants are transformed into less hazardous compounds with a diminished impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore photo-Fenton process is much more efficient in the •OH generation compared with the conventional Fenton process [76,77]. Viewing this fact, many studies have been performed to employ photo-Fenton technique for micropollutant removal, and removal efficiency depends greatly on the pH of reaction solution, Fe 2+ and H2O2 dosages [63,76,[78][79][80][81][82]. Usually, acidic pH (lower than 3) is required in Fenton processes to obtain good solubility of the iron ions [83], which is one of the main drawbacks of Fenton based techniques.…”
Section: Photo-fenton Processesmentioning
confidence: 99%